2020
DOI: 10.2147/dddt.s265066
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quercetin Inhibits Adenomyosis by Attenuating Cell Proliferation, Migration and Invasion of Ectopic Endometrial Stromal Cells</p>

Abstract: To evaluate the effects of quercetin on proliferation, invasion and migration of endometrial stromal cells (ESCs) from adenomyosis patients. Methods: Primary ectopic ESCs (EESCs) and eutopic ESCs (EuESCs) were obtained and purified from patients undergoing total hysterectomy for adenomyosis and identified by immunocytochemistry staining. The cytotoxicity and inhibition rate were determined by CCK-8 assay to obtain the IC 50 value. Cell proliferative, migratory, and invasive abilities were detected by BrdU, wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…MMP2, MMP9 and ezrin are known to be involved in cell migration, and vimentin is an important marker for mesenchymal/motile phenotype 30,31 . Therefore, to determine the mechanism of action of activin A and FST on d‐MESCs migration, MMP2, MMP9, Vimentin and Ezrin expressions were analysed by Western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP2, MMP9 and ezrin are known to be involved in cell migration, and vimentin is an important marker for mesenchymal/motile phenotype 30,31 . Therefore, to determine the mechanism of action of activin A and FST on d‐MESCs migration, MMP2, MMP9, Vimentin and Ezrin expressions were analysed by Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…MMP2, MMP9 and ezrin are known to be involved in cell migration, and vimentin is an important marker for mesenchymal/motile phenotype. 30 , 31 Therefore, to determine the mechanism of action of activin A and FST on d‐MESCs migration, MMP2, MMP9, Vimentin and Ezrin expressions were analysed by Western blotting. The results showed that the expressions of MMP9 and Ezrin were upregulated significantly after FST stimulation, and only slightly increased after activin A treatment (Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…The above screening results are consistent with the literature. 46–49 These inhibitors have been demonstrated in diseases related to matrix metalloproteinases, indicating that the method can be applied to the screening of MMP inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, miR-141-3p was confirmed as a downstream molecule of circ_0061140. Increasing studies showed that cell migration and invasion played important roles in the pathogenesis of adenomyosis [38-40]. Accumulating evidence has revealed that miR-141-3p suppressed cell motility of tumor cells in multiple malignancies [41-43].…”
Section: Discussionmentioning
confidence: 99%